Corrigendum to “Dehydration of jambolan [Syzygium cumini (L.)] juice during foam mat drying: Quantitative and qualitative changes of the phenolic compounds” (Food Research International (2017) (102) (32–42)(S0963996917306518)(10.1016/j.foodres.2017.09.068)) - Tavares, Iasnaia Maria de Carvalho [UNESP]; Nogueira, Tuany Yuri Kuboyama [UNESP]; Mauro, Maria Aparecida [UNESP]; Gómez-Alonso, Sergio; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP]; Hermosín-Gutiérrez, Isidro; Lago-Vanzela, Ellen Silva [UNESP] (My University, 2018)
The authors regret “that the name of the first author was wrong and we did not detect at time this error during the processing of the article. The correct name for the first author is Iasnaia María de Carvalho Tavares (I.M.C. Tavares).” The authors would like to apologise for any inconvenience caused.